The Effect of Authenticity and Creativity in Advertising: How Digital Advertisements Shape Perceived Brand Authenticity and Brand Image - Gökgöz, Kübra; Bozkurt, Yasemin (International Review of Management and Marketing, 2026)
This study examined the effects of advertising creativity and authenticity in digital advertisements on perceived brand authenticity and brand image within the framework of Attribution Theory. These variables, which have mostly been addressed separately in the literature, were tested using a holistic model to; reveal the impact of the creative and authentic characteristics of advertising on consumers’ brand evaluations. The research was designed using a quantitative method; data were collected through an online survey from 321 consumers in Turkiye who were exposed to digital advertisement. The proposed hypotheses were tested by using Structural Equation Modeling (SEM). These findings indicate that advertising creativity positively affects advertising authenticity. Advertising authenticity significantly and positively influences both perceived brand authenticity and brand image; emerges as the strongest direct determinant of brand image. In contrast, the direct effects of advertising creativity and perceived brand authenticity on brand image were not significant. This study integrates the fragmented approach in digital advertising literature by examining advertising creativity and authenticity within a single model. These findings demonstrate that advertising authenticity plays a prominent role in the formation of brand image, whereas creativity indirectly supports this process. In this respect, the research offers a strategic contribution by showing that, in digital media, brand image may be shaped not by abstract and general brand evaluations; but by the creative and authentic qualities of the advertisement directly experienced by the consumer.